Hubungan antara Self-Efficacy dan Persepsi Siswa Terhadap Metode Teacher Centered Learning (TCL) dengan Student Engagement pada Siswa SMA di Kota Padang - Ayesha Rizqieta Martania Putri; Devi Rusli (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to examine the relationship between self-efficacy and students’ perceptions of the Teacher-Centered Learning (TCL) method with student engagement among high school students in Padang City. This research employed a quantitative correlational design with 206 students selected using purposive sampling. The instruments used were the Student Engagement Scale by Fredricks et al. (2004) adapted by Sa’adiyah & Qudsyi (2016), the General Self-Efficacy Scale (Novrianto et al., 2019), and a perception scale of the TCL method developed by the researcher. Data analysis was conducted using the Product Moment correlation. The results showed a significant relationship between self-efficacy and students’ perceptions of the TCL method with student engagement. Correlation analysis indicated that self-efficacy had a positive and significant relationship with student engagement (r = 0.661; p < 0.001), and students’ perceptions of the TCL method also had a positive and significant relationship with student engagement (r = 0.540; p < 0.001). The product moment analysis further revealed that both predictor variables together explained 46.8% of the variance in student engagement (R = 0.684; R² = 0.468; p < 0.001). These findings indicate that self-efficacy and students’ perceptions of the TCL method play an important role in shaping student engagement among high school students in Padang City.